Pengaruh Kompleksitas Operasi Perusahaan, Ukuran Kap dan Audit Tenure terhadap Audit Delay - Intan Puspa Dewi; Auliffi Ermian Challen (Lembaga Penelitian Universitas YARSI, 2018)
This research is conducted in order to analyse the relationship between complexity of the company’s, size of public accounting firm and tenure audit to audit delay to the manufacturing companies listed in the Indonesia Stock Exchange in the period 2011-2015. The sample in this research was secondary data and selected by using purposive sampling method. The population of this research consist of 143 companies listed in the Indonesia Stock Exchange (IDX). And samples used in this research as many as 95 companies. The analytical method used is multiple linear regression analysis. The result of this research showed that size of public accounting firm have negative impact to the audit delay, while the complexity of the company’s and tenure audit do not have effect to the audit delay.